Improving drawbell drill and blast performance in block caving: field-based improvements from Panel 0, Oyu Tolgoi underground - Muis, A; Demberel, B (Caving 2026: Sixth International Conference on Block and Sublevel Caving, 2026)
Drawbell establishment is a critical stage in block cave mining as it directly affects cave initiation, early material flow, and overall production reliability. At the Oyu Tolgoi underground mine, several operational challenges were observed during drawbell development in Panel 0, particularly related to single-sided drawbell configurations, brow stability, and uncertainty in undercut–drawbell connectivity. This paper presents a series of practical design and operational improvements developed to address these challenges. The work focuses on 3 areas: improving drill and blast performance for single-sided drawbells, strengthening brow set protection, and introducing a verification approach to confirm connectivity between the undercut and drawbell. The proposed improvements were developed based on operational observations, blast performance reviews, and drawbell trials conducted in Panel 0. Early applications indicate improvements in drawbell reliability, brow stability, and readiness for production. Quantitative results and operational performance indicators are discussed to demonstrate the effectiveness of the revised approach.
Keywords: block caving; drawbell design; single-sided drawbell; brow set protection; undercut connection; cave initiation; operational controls